Effect of U-92032, T-Type Ca(2+)Channel Blocker, on Rats with Genetic Absence Epilepsy - YANANLI, HASAN RACİ; GÜLHAN, REZZAN (KARGER, 2020)
Introduction:Absence epilepsy is associated with diffuse spike-and-wave discharges (SWD) on the electroencephalogram (EEG). Recent studies have demonstrated that the primary somatosensory cortex is also implicated in the generation of the SWDs.Objective:This study investigated the effects of systemic and local administrations of U-92032 into the brain of Genetic Absence Epilepsy Rats from Strasbourg (GAERS).Methods:GAERS animals underwent stereotaxic surgery for the placement of EEG recording electrodes and guide cannulas for U-92032 administration into the lateral ventricle (intracerebroventricular [i.c.v.]), upper lips area (S1Ulp) or barrel field area (S1B) of primary somatosensory cortex. Following 7 days of recovery, electrical activity was recorded continuously for 1 h before and 6 h after intraperitoneal (0.25; 1; 5 mg/kg i.p.) or local U-92032 or dimethyl sulfoxide (DMSO) injections.Results:No changes were detected in the cumulative duration, mean duration, and number of SWDs following i.p. U-92032 injections. Local i.c.v. injections of U-92032 caused a significant decrease in the cumulative duration (i.c.v., 50 and 100 nmol/L), mean duration (i.c.v., 50, 100, and 250 nmol/L), and the number (i.c.v., 250 nmol/L) of SWDs compared to DMSO groups. Intra-cortical (S1Ulp and S1B) U-92032 injections caused a significant decrease in all 3 parameters compared to DMSO groups, as well.Conclusion:Intra-cortical injection of U-92032 caused almost complete removal of SWDs in GAERS and i.c.v. administration resulted in a significant reduction. However, systemic i.p. administration did not cause a significant change with the applied -doses.
Keywords: Epilepsy; Calcium channel blocker; Spike-and-wave discharges; Cortex; Rats; CALCIUM-CHANNEL; MOLECULAR CHARACTERIZATION; ETHOSUXIMIDE; SEIZURES; EXPRESSION; THALAMUS; CLONING; MEMBERS; MODEL